2000
DOI: 10.1046/j.1432-1327.2000.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic study of the reaction of NAMI, a novel ruthenium(III)anti‐neoplastic complex, with bovine serum albumin

Abstract: The reaction of Na [transRuCl 4 Me 2 SO(Im)] (NAMI; where Im is imidazole), a novel anti-neoplastic ruthenium(III) complex, with BSA, was studied in detail by various physico-chemical techniques. It is shown that NAMI, following chloride hydrolysis, binds bovine serum albumin tightly; spectrophotometric and atomic absorption data point out that up to five ruthenium ions are bound per albumin molecule when BSA is incubated for 24 h with an eightfold excess of NAMI. CD and electronic absorption results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
98
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 18 publications
(23 reference statements)
9
98
1
6
Order By: Relevance
“…Although Ru(III)-based NAMI-A shows promising results in animal models and is currently in early clinical trials, 15,17,33 it does not have a single target since it interacts with DNA, 39 collagen 40 and major plasma proteins like serum albumin. 41 This is in great contrast with C225, a chimeric antihuman EGF-R MAb that specifically blocks ligand binding and functional activation of this receptor. 24,37,42 However, repeated exposure of some tumors to C225 can lead to acquisition of resistance to this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Ru(III)-based NAMI-A shows promising results in animal models and is currently in early clinical trials, 15,17,33 it does not have a single target since it interacts with DNA, 39 collagen 40 and major plasma proteins like serum albumin. 41 This is in great contrast with C225, a chimeric antihuman EGF-R MAb that specifically blocks ligand binding and functional activation of this receptor. 24,37,42 However, repeated exposure of some tumors to C225 can lead to acquisition of resistance to this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…24,37,42 However, repeated exposure of some tumors to C225 can lead to acquisition of resistance to this treatment. 24,41 To widen the scope of Ru(III)-based NAMI-like drugs, our study was devoted to an Ru(II)-based complex, which demonstrated a significant antitumor effect irrespective of p53 status against cell monolayers, unlike cisplatin. 9,10 However, we discovered that A431 spheroids, which overexpress EGF-R, 24 like many human carcinomas, 37 are not susceptible to either C225 or RuCl 2 (KTZ) 2 but to the joint use of both agents.…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18] By analogy with platinum complexes, it was originally assumed that DNA binding was the main reason for the anticancer activity of ruthenium complexes. 16,[19][20][21] While the ability of ruthenium complexes to bind to DNA has been demonstrated, [22][23][24][25] in particular for arene ruthenium ethylenediamine complexes, 26,27 it was also observed that DNA binding of ruthenium was weaker and different from that observed for platinum complexes. 22 Recent examples of rationally designed metal complexes that inhibit enzymatic activities involved in cancer proliferation were investigated, 28,29 including ruthenium half-sandwich complexes that bind to specific enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of such selected metal based compounds contain metal-oxygen (M-O) hemilabile bonds e.g., (M-OvM-OH 2 ) [13,14,22] or (M-SOMe 2 ) [16] which have shown interesting and potential anti-tumor or antibacterial activity (Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…12.5 mg/ mL [15]. Na[trans-RuCl 4 (Me 2 SO)(Im)] (Im ¼ imidazole), a ruthenium(III) complex shows encouraging antitumour and anti-metastatic properties [16].…”
Section: Introductionmentioning
confidence: 99%